2022
DOI: 10.3390/jcm11061569
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Bulking in the Treatment of Stress and Mixed Female Urinary Incontinence: Results from a Multicenter Cohort and Predictors of Clinical Outcomes

Abstract: The aim of the present study is to analyze the outcomes of urethral bulking in the treatment of non-neurogenic female stress and mixed urinary incontinence and to assess predictors of clinical outcomes. We retrospectively included all consecutive patients affected by stress or mixed urinary incontinence and treated with urethral bulking. Outcomes were evaluated via the PGI-I questionnaire and the 24-h pad test. Between January 2010 and January 2020, we treated 216 patients (Bulkamid n = 206; Macro-plastique n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A subsequent 7-year follow-up study has demonstrated cure rates of 67.1% [78]. Cure rates were worse for those with strong urinary urgency symptoms [77,79].…”
Section: Urethral Bulking Agentsmentioning
confidence: 97%
“…A subsequent 7-year follow-up study has demonstrated cure rates of 67.1% [78]. Cure rates were worse for those with strong urinary urgency symptoms [77,79].…”
Section: Urethral Bulking Agentsmentioning
confidence: 97%
“…A retrospective dataset analysis of women over 65 years showed that patients receiving bulking agents were notably sicker and have a shorter life expectancy compared to those undergoing sling insertion, suggesting these factors guide patient selection [ 55 ]. Bulking therapy is more successful for patients with mild SUI [ 45 , 56 , 57 ] or with ISD [ 58 ]. Patients younger than 60 years preferred an office setting rather than an operation theatre [ 59 ].…”
Section: Bulking Agents To Treat Suimentioning
confidence: 99%
“…As such, much of the recent literature has focused on the use of PAHG, and many of the trials on PAHG injection includes women both of an older age (over 60 years old) and/or with MUI, including some longer-term outcomes. A recent retrospective review reported outcomes of 216 consecutive patients treated with either PAHG or Macroplastique (polydimethylsiloxane macroparticles suspended within polyvinylpyrrolidone hydrogel) with a mean age of 66 years old and included 36% with MUI (including preoperative DO in 25%) [94]. At 12-month follow up, 70% of patients declared themselves "improved" or "very improved", and 33% were completely dry.…”
Section: Surgical Management Of Stress Urinary Incontinencementioning
confidence: 99%